Ketamine does not enhance the quality of recovery following laparoscopic cholecystectomy: a randomized controlled trial - Moro, E. T.; Feitosa, I. M.P.S.S.; de Oliveira, R. G.; Saraiva, G. F.P.; Rosalino, R.; Marossi, V. P.; Bloomstone, J. A.; Navarro, L. H.C. [UNESP] (Wiley, 2017)
Background: Ketamine has been used as part of the multimodal analgesia technique in the acute perioperative period. The effect of perioperative intravenous small-dose ketamine on the quality of recovery from the patient point-of-view has not been assessed. We hypothesized that low-dose ketamine would enhance recovery following laparoscopic cholecystectomy under total intravenous anesthesia. Methods: One hundred thirty five patients undergoing laparoscopic cholecystectomy were enrolled in this randomized, double-blind placebo-controlled trial. Subjects were randomly assigned to one of three groups: saline, ketamine 0.2 mg/kg, or ketamine 0.4 mg/kg immediately following the induction of anesthesia and before skin incision. The primary endpoint was assessed using the Quality of Recovery Questionnaire (QoR-40), a 40-item quality of recovery scoring system. In addition, early clinical recovery variables, such as time to eye opening, occurrence of nausea and vomiting, pain score, analgesic use, and length of PACU stay were assessed. Results: No differences were detected in the total or individual dimension scores of the QoR-40 questionnaire. The incidence of nausea, vomiting, and other complications did not differ among the three groups. Conclusions: Small doses of ketamine do not improve the quality of recovery after remifentanil-based anesthesia for laparoscopic cholecystectomy.